2017
DOI: 10.1093/europace/eux120
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of selective and non-selective His bundle pacing on cardiac electrical and mechanical synchrony

Abstract: Selective His bundle pacing and high-output NS-HBP could restore normal electrical and LV mechanical synchrony.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 22 publications
0
53
0
8
Order By: Relevance
“…Although limited studies support the concept that nonselective HB pacing is hemodynamically equivalent to selective pacing, 32,33 we do not have concrete clinical evidence. Selective HB pacing is certainly closer to physiology and offers a straightforward electrocardiographic diagnosis of the presence/loss of HB capture and also allows to easily offset the HV interval from atrioventricular delay during DDD pacing.…”
Section: Selective Vs Nonselective Hb Capturementioning
confidence: 80%
“…Although limited studies support the concept that nonselective HB pacing is hemodynamically equivalent to selective pacing, 32,33 we do not have concrete clinical evidence. Selective HB pacing is certainly closer to physiology and offers a straightforward electrocardiographic diagnosis of the presence/loss of HB capture and also allows to easily offset the HV interval from atrioventricular delay during DDD pacing.…”
Section: Selective Vs Nonselective Hb Capturementioning
confidence: 80%
“…A study by Fozzard and Schoenberg concerning His bundle chronaxie assessed in the milieu of experimental ex vivo models reported chronaxie values of approximately 0.23 ms 27. Selective vs non-selective HB captureAlthough limited studies support the concept that non-selective HB pacing is hemodynamically equivalent to selective pacing,28,29 we do not have concrete clinical evidence. Selective HB pacing is certainly closer to physiology and offers straightforward ECG diagnosis of presence/loss of HB capture and also allows to easily offset HV interval from atrioventricular delay during DDD pacing.…”
mentioning
confidence: 89%
“…In 2000, the utility of HBP was first reported in patients with atrial fibrillation (AF) and cardiomyopathy undergoing atrioventricular (AV) node ablation and left ventricular (LV) function was shown to improve after HBP . Recent studies and meta‐analyses have demonstrated the superiority of HBP in preserving electrical synchrony and LV function compared to conventional right ventricular pacing . Currently, cardiac resynchronization therapy (CRT) is the standard‐of‐care therapy for the patients with heart failure and LV dyssynchrony.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recent studies and meta-analyses have demonstrated the superiority of HBP in preserving electrical synchrony and LV function compared to conventional right ventricular pacing. [2][3][4][5] Currently, cardiac resynchronization therapy (CRT) is the standard-of-care therapy for the patients with heart failure and LV dyssynchrony. However, approximately 30% of the patients show no response.…”
Section: Introductionmentioning
confidence: 99%